2011
DOI: 10.1155/2011/496189
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Content Varies with Pathological Characteristics of Breast Cancer

Abstract: Changes in mitochondrial DNA (mtDNA) content in cancers have been reported with controversial results, probably due to small sample size and variable pathological conditions. In this study, mtDNA content in 302 breast tumor/surrounding normal tissue pairs were evaluated and correlated with the clinico-pathological characteristics of tumors. Overall, mtDNA content in tumor tissues is significantly lower than that in the surrounding normal tissues, P < 0.00001. MtDNA content in tumor tissues decreased with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 50 publications
(85 reference statements)
5
44
2
Order By: Relevance
“…These increases were regarded as a compensation process to overcome the oxidative damages from cigarette smoking and to maintain proper mitochondrial function (19). Concerning BIDCs, a decrease in mtDNA copy number was reported in some research articles (37)(38)(39). Nevertheless, we demonstrated a significantly higher mtDNA copy ratio in BIDCs that harbored negative-ER, negative-PR, positive-p53 or high Ki-67 expression.…”
Section: Discussionmentioning
confidence: 52%
“…These increases were regarded as a compensation process to overcome the oxidative damages from cigarette smoking and to maintain proper mitochondrial function (19). Concerning BIDCs, a decrease in mtDNA copy number was reported in some research articles (37)(38)(39). Nevertheless, we demonstrated a significantly higher mtDNA copy ratio in BIDCs that harbored negative-ER, negative-PR, positive-p53 or high Ki-67 expression.…”
Section: Discussionmentioning
confidence: 52%
“…Based on this study, it has been deduced that tumor cells do not completely depend on the mitochondria for oxidative phosphorylation to provide energy. Dani et al stated that the higher glycolytic capacity of tumor cells may be due to the increased growth and nutrient demands of tumor cells, which was not against the theory of the importance of oxidative phosphorylation for the survival and growth of tumors (33,34). It was due to the higher nutrient and oxygen demands that numerous tumors continue to grow in vivo via the induction of neovascularization (35).…”
Section: Correlation Between Mtdna Mutations and Tumorsmentioning
confidence: 99%
“…Later in 2009, Fan et al reported that basing on clinical case analysis 82% of malignant breast tumor accompany with lower mtDNA level compared to normal breast tissue [66] . In 2011, the mtDNA content in breast cancer was tested again in 302 cancerous breast tissues and in their corresponding surrounding normal tissues, the result also showed the cancerous tissue contains lower mtDNA content than normal ones [67] .…”
Section: Mtdna Content and Cancermentioning
confidence: 99%